A constant state of failure - Harris, Terri Catherine (Rhodes University, 2026)
Access to reliable water is a fundamental human right, yet Makhanda, a small town in South Africa, faces ongoing challenges in water service delivery, leading to widespread dissatisfaction. This research adopts a socio-technical systems approach, leveraging Human Factors and Ergonomics (HFE) methods, to analyse and these issues within Makhanda’s Eastern water management system. Through the workplace observations and semi-structured interviews, of twelve municipal water officials, the study identified key interactions between, individuals, tasks, tools, organisations, and their working environments. Data were mapped using models based on the Systems Engineering Initiative for Patient Safety (SEIPS) framework, and were further analysed with a deductive and inductive approach revealing recurring systemic themes, that persisted as either facilitators or barriers to the water systems’ functioning. The findings highlighted critical barriers such as mismanagement of finances, insufficient funding, resource shortages, staff vacancies, and brittle infrastructure prone to frequent breakages. These barriers were linked to poor systemic vertical integration, ineffective feedback loops, and a drift toward failure due to unattended alarm feedback signals, delayed responses and inadequate/ ineffective counter gradients. While some barriers are deeply rooted and time-consuming to address, a key first step is leveraging resilient water system employees. Strengthening communication and recognizing individual contributions can enhance vertical integration, improving mishap reporting and response times. Streamlining processes, reducing job vacancies, and fostering a culture of learning will further boost efficiency. These efforts will help mitigate errors, enhance water service delivery, restore community trust, and support sustainable water management in Makhanda.
characterisation of the water management system of a small South African town
Keywords: Human engineering (http://id.loc.gov/authorities/subjects/sh85062867); Sociotechnical systems (http://id.loc.gov/authorities/subjects/sh2015002635); Water resources system (https://www.wikidata.org/wiki/Q115161040); Socio-ecological system (https://www.wikidata.org/wiki/Q7552762); Sustainability (http://id.loc.gov/authorities/subjects/sh2009000375); Wicked problem (https://www.wikidata.org/wiki/Q2891260)